An innovative synthesis pathway to benzodioxanes: the peculiar reactivity of glycerol carbonate and catechol. Issue 2 (2nd January 2019) - Tabanelli, T.; Giliberti, C.; Mazzoni, R.; Cucciniello, R.; Cavani, F.
Abstract : A peculiar reactivity of glycerol carbonate (GlyC) as an innovative and highly reactive alkylating agent for phenolic compounds is investigated in this article. Abstract : A peculiar reactivity of glycerol carbonate (GlyC) as an innovative and highly reactive alkylating agent for phenolic compounds is investigated in this article. In particular, 2-hydroxymethyl-1, 4-benzodioxane (HMB), a key intermediate for the pharmaceutical industry, has been selectively synthesized by the reaction of a slight excess of GlyC with catechol in the presence of a basic catalyst (NaOCH3, Na-mordenite, MgO), without requiring a reaction solvent. Both reagents have been quantitatively converted in just one hour at 170 °C with a HMB yield, up to 88%, in the presence of a homogeneous basic catalyst (NaOCH3 ). Notably, the main side product, the HMB isomer, may be an interesting intermediate for the synthesis of calone analogues, which are important scaffolds used in fragrances. A detailed mechanistic study, supported by kinetics, GC-MS, and HMBC NMR characterization, is also reported. Accordingly, this paper describes a completely innovative and greener synthesis pathway to benzodioxanes.